Neuronal substrates of sleep and epilepsy - Steriade, Mircea (Cambridge University Press, 2003)
Sleep and epilepsy are common bedfellows, as a series of epileptic fits can occur during the state of sleep with slow electroencephalogram waves. The author describes for neuroscientists and clinicians the different states, the neuronal operations that account for normal states and the cellular mechanisms underlying types of epileptic seizures.